Peran Program Arabic Tajwid Class (ATC) dalam Meningkatkan Pemahaman dan Kemampuan Baca Al-Qur’an Santri TPQ Roudlotul Nurul Amin di Kelurahan Majaran - Alda Novian Anam; Amrin Keliata; Laila Zahrotun Nisa; Munirotul Fuad; Nazwa Putri Utami; Nur Zahro Zakiyahturrohmah; Miftahulfadlik Dabamona; Rabiudin Rabiudin (PANTAK: Jurnal Penelitian Tindakan Kelas, 2025)
This study aims to analyze the role of the Arabic Tajwid Class (ATC) program in improving students' understanding of tajwid and Quranic recitation skills at the Roudlotul Nurul Amin Islamic Boarding School (TPQ) in Majaran Village. Using descriptive qualitative methods through observation, interviews, documentation, and direct researcher involvement, the study found that students initially experienced difficulties in reading the Quran, pronouncing letters, and reading rules of tajwid. ATC was implemented in stages through pronunciation practice, repetition, reading examples, and interaction-based material reinforcement, along with the introduction of simple vocabulary. The results showed that students' ability to apply the rules of tajwid significantly improved, followed by an increased understanding of the rules of tajwid. Supporting factors for the program's success included organized materials, additional study time, and support from teachers. While inhibiting factors included differences in students' basic abilities and limited study time. Overall, ATC proved effective in improving students' understanding of tajwid and the quality of Quranic recitation and was effective as a learning companion program.